Influence of a reverse delta-type add-on device on wake vortex alleviation - Altaf, Alamaan; Thong, Tanboon; Omar, Ashraf Ali; Asrar, Waqar (American Institute of Aeronautics and Astronautics Inc. (AIAA), 2016)
Particle image velocimetry was used in a low-speed wind tunnel to investigate the effect of interactions of vortices produced by a wingtip of a half-span wing (NACA 23012 in landing configuration) and a slender reverse delta-type add-on device placed near the tip on the upper surface of the half-span wing. This work investigates the characteristics of the vortex interactions generated downstream in planes perpendicular to the freestream direction and their dependence on angles of attack at a chord-based Reynolds number of Rec = 2.75 × 105. It was found that the add-on device significantly reduced the tangential velocity, vorticity, and circulation magnitude by up to 82.9, 92.6, and 42.8%, respectively, and increased the resultant vortex core radius by a factor of 6.57.Asix-component force balance was used to obtain the aerodynamic performance of the half-span wing model with a reverse delta-type add-on device. It was found that the reverse delta-type add-on device marginally affected the aerodynamic performance of the halfspan high-lift configuration wing model.